ChemInform Abstract: Improved Zinc‐Catalyzed Simmons—Smith Reaction: Access to Various 1, 2, 3‐Trisubstituted Cyclopropanes. Issue 34 (26th August 2014) - Levesque, Eric; Goudreau, Sebastien R.; Charette, Andre B.
Abstract The high reactivity of aryldiazomethanes towards zinc allows for catalytical generation of the intermediary carbenoids.